PERAN BUDAYA LOKAL DAN KENYAMANAN DALAM MENINGKATKAN LOYALITAS WISATAWAN PADA DESTINASI WISATA BAHARI DI BANTEN - Asfar, Andi Hasryningsih; Mahendra, Yoga; Saputra, Saripudin (National Conference on Applied Business, Education, & Technology (NCABET), 2024)
This study aims to analyze the role of local culture and the comfort of facilities in enhancing tourist loyalty at marine tourism destinations in Banten, focusing on Pantai Anyer, Pantai Tanjung Lesung, and Pantai Bagedur. Tourist loyalty, which is increasingly important in tourism competition, is influenced by various factors, including emotional attachment derived from local culture and comfort while enjoying the destination. Using a qualitative approach and phenomenological design, this research explores the perceptions and experiences of tourists through in-depth interviews, participatory observations, and analysis of documentation from related tourism sources. The findings indicate that local culture, including traditional art performances, local cuisine, and interactions with cultural values, creates a unique and authentic experience that strengthens tourists' attachment to the destination. This emotional attachment significantly increases tourists' desire to return and recommend the destination to others. Furthermore, the comfort of facilities, such as the availability of clean restrooms, adequate parking, and accessibility, serves as an essential supporting factor. Tourists who feel comfortable with the provided facilities are more likely to have positive and memorable experiences. In conclusion, the synergy between local culture and facility comfort can create meaningful and comprehensive tourism experiences, ultimately reinforcing tourist loyalty. Recommendations from this study suggest that managers of marine tourism destinations in Banten continue to promote local culture and improve the quality of facilities to create more appealing experiences and sustainably encourage tourist loyalty